Dental laser education and knowledge among students from dental colleges of Mumbai and Pune City: A questionnaire study - Swapnil Rangnath Kadam; Gulam Anwar Naviwala; Aaditya Mukesh Panchal; Sumedha Soma Shastri Nishtala; Vikrant Ravindra Pardeshi (Wolters Kluwer Medknow Publications, 2017)
Introduction: Lasers in dentistry are considered to be a new technology which is being used in clinical dentistry to overcome some of the drawbacks posed by the conventional dental procedures. Aim: This study aims to assess dental laser education and knowledge among students from dental colleges of Mumbai and Pune city. Materials and Methods: A cross-sectional study was conducted among 150 randomly selected dental students from four dental colleges of Mumbai and Pune city using a questionnaire. Results: All the 150 participants knew what dental laser was, but when asked about the practical experience, only 10 (6.7%) participants had previous dental laser practice experience. Around 126 (84%) participants agreed that both theoretical and practical laser education is needed. Lack of clinical experience (35.3%) followed by lack of knowledge (25.1%) and price of laser unit (22.5%) were the main reasons for the lack of use of dental lasers according to the study participants. Conclusion: Undergraduate dental students had inadequate laser education and insufficient knowledge regarding dental lasers. More education about dental lasers should be added to the curriculum of undergraduate program since it is highly essential for students to know about newer technologies and apply it in their practice.